Animal feeds from transgenic crops: a biosafety perspective - SINGH, VIR; KUMAR, ASHOKA; BOHRA, BABITA; NAUTIYAL, NANDA; NEGI, VRINDA (The Indian Journal of Animal Sciences, 2016)
There are many biosafety issues pertaining to transgenic crops. Long-term implications of the transgenics for livestock and human health need to be identified and addressed. Researchers dealing with transgenic crops have brought to the fore many of their advantages and disadvantages. All possible effects of transgenic feeds must be tested before the transgenic crops are utilized to derive feeds from them for livestock feeding. Human health can be affected directly through consumption of foods from transgenic crops as well as through livestock products if feeds are derived from these crops. This paper attempts to examine some pertinent issues relating to possible effects of feeding livestock with feeds from transgenic crops and presents a perspective on how to evaluate such feeds to ensure biosafety when transgenic crops or their residues are used as feeds.